Cryptolaria prima Busk 1857 - Cantero, Álvaro Luis Peña (Zenodo, 2023)
Cryptolaria prima Busk, 1857 (Fig. 4e–h) Cryptolaria prima Busk 1857: 173, pl. XVI; Vervoort & Watson, 2003: 55–57 (synonymy). Material examined. TRIP 5582/42 , at least two colonies up to 180 mm high, with coppiniae (NIWA 131516). Description. Stems up to 180 mm high, completely polysiphonic. Stems giving rise to unbranched pinnae, up to 47 mm long, arranged in one plane in sub-opposite pairs. Pinnae with approximately constant diameter for most of their length, then tapering very gently distally, ending in a quite rounded tip. A few pinnae developing into branches or lower-order stems and giving rise in turn to pinnae. Hydrothecae forming four longitudinal rows with an X arrangement. Hydrothecae not protruding far from peripheral tubes. Hydrotheca approximately cylindrical, distally bent outwards, adnate for about two-thirds of its adcauline wall. Free part of adcauline wall convex; adnate part straight or slightly convex. Abcauline wall roughly straight basally but concave distally. Aperture circular, directed upwards and outwards; rim even, often with renovations. Nematothecae cylindrical, resting on a short pedicel; aperture circular. Measurements (in µm). Hydrotheca : abcauline length 280–300, free adcauline length 140–170, adnate adcauline length 270–280, adcauline length 420–440, diameter at aperture 120–130, diameter at diaphragm 90. Nematotheca : height 80, diameter at aperture 25, maximum diameter 30, pedicel length 20. Remarks. I refer this material to C. prima because of the presence of four longitudinal rows of hydrothecae with an X-arrangement, i.e. there are two alternating series on opposite sides of the pinnae. Present material also agrees with Busk’s species in the shape of the gonothecae, with the aperture laterally placed on a dome-shaped, hood-like structure, without the sharp projection typical of Cryptolaria pectinata (Allman, 1888). Ecology and distribution. The material studied was collected at a depth of 175−206 m, off Snares Islands. Coppiniae present in March. The species is ...